Industrial Relations and Macroeconomic Performance : An Application to Spain. (IMF Working Papers; Working Paper ;, 1990)
The paper analyzes the macroeconomic implications of different systems of industrial relations. After reviewing the relevant literature, and analyzing cross-country evidence, the paper focuses on the experience of centralized bargaining characterizing Spain in the period 1979-86. The paper argues, in accordance with the literature and the cross-country evidence, that the centralization of bargaining yielded positive macroeconomic effects in Spain, and thus that the shift toward a more decentralized setting after 1987 carries several risks. This conclusion is based on an empirical analysis of the wage setting process and of the evolution of labor shares in income.